Dynamics of over body weight among women of young and mature age of open city population: twenty years of trends - M. M. Kayumova; E. I. Gakova (Сибирский научный медицинский журнал)
Introduction Epidemiological studies indicate a high prevalence of overweight in all economically developed countries of the world, its growth was registered everywhere by the beginning of the century. According to the World Health Organization, over 30 % of the world’s inhabitants have overweight, and therefore, WHO has recognized it as a new non-infectious «21st century epidemic». The aim of the study was to determine the twenty-year dynamics of the prevalence of overweight among young and mature women in the open population of the mid-urban city of Western Siberia. Material and methods. Simultaneous epidemiological studies were conducted on representative samples in 1996 and 2016 among women of 25–64 years old with the allocation of categories of young and mature age. Overweight was determined based on body mass index (BMI), with BMI ≥ 30.0 obesity was recorded, with BMI ≥ 25.0 – overweight. Results. Over 20 years of monitoring the open population of the mid-urbanized city of Western Siberia, a positive trend has been established to reduce the prevalence of overweight in the category of young women. In the age range in relation to the prevalence of BMI according to the first and second screenings in the open urban population, a negative trend has been established for an increase in the prevalence of obesity and overweight among young women during the transition from the third to the fourth decade of life. According to the first screening in an open urban population, a negative trend was found to increase the prevalence of obesity and overweight among mature women during the transition from the fifth to the sixth decade of life, according to the second screening in the same groups, to an increase in the prevalence of overweight. Conclusion. Changes in population health at certain time intervals, depending on socio-economic, environmental, and behavioral factors, in each time period and in each individual population require specific, epidemiologically-related preventive measures.